2007
DOI: 10.1016/j.ydbio.2007.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Dystroglycan regulates structure, proliferation and differentiation of neuroepithelial cells in the developing vertebrate CNS

Abstract: In the developing CNS alpha- and beta-dystroglycan are highly concentrated in the endfeet of radial neuroepithelial cells at the contact site to the basal lamina. We show that injection of anti-dystroglycan Fab fragments, knockdown of dystroglycan using RNAi, and overexpression of a dominant-negative dystroglycan protein by microelectroporation in neuroepithelial cells of the chick retina and optic tectum in vivo leads to the loss of their radial morphology, to hyperproliferation, to an increased number of pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 74 publications
3
21
0
Order By: Relevance
“…4 b-d). Confirming a previous report [Schroder et al, 2007], the ␤ -dystroglycan antibody used in this work, generated against a peptide in human ␤ -dystroglycan that is 100% conserved in chicken ␤ -dystroglycan, recognized a band of expected size (43 kDa) in Western blot with stage HH1 and HH3-4 embryonic lysates ( fig. 4 g), suggesting that this antibody also specifically recognizes ␤ -dystroglycan in chicken tissues.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…4 b-d). Confirming a previous report [Schroder et al, 2007], the ␤ -dystroglycan antibody used in this work, generated against a peptide in human ␤ -dystroglycan that is 100% conserved in chicken ␤ -dystroglycan, recognized a band of expected size (43 kDa) in Western blot with stage HH1 and HH3-4 embryonic lysates ( fig. 4 g), suggesting that this antibody also specifically recognizes ␤ -dystroglycan in chicken tissues.…”
Section: Resultssupporting
confidence: 89%
“…This region is 100% conserved in the chicken ␤ -dystroglycan protein. The antibody was reported to cross-react with chicken dystroglycan according to the company product datasheet and published literature [Schroder et al, 2007], confirmed by us with Western blot analysis of early embryonic lysates ( fig. 4g).…”
Section: Methodssupporting
confidence: 64%
See 1 more Smart Citation
“…Although the role of b1-integrins in radial glial cells during development has been well studied (Beggs et al, 2003;Belvindrah et al, 2007a;Georges-Labouesse et al, 1998;Haubst et al, 2006;Herms et al, 2004;Schroder et al, 2007), still very little is known about the interaction between astrocytes and the leptomeningeal and vascular BMs in the postnatal and adult brain.…”
Section: Discussionmentioning
confidence: 99%
“…Transfection and staining of HEK293 cells Full-length complementary DNA (cDNA) coding for human LRP4 (huLRP4) was obtained from Imagenes GmbH (Berlin, Germany) and subcloned into the pMES vector [28], which allows identification of transfected cells by simultaneous expression of enhanced green fluorescent protein (EGFP). Successful cloning and surface expression of LRP4 was confirmed by Western blotting and immunocytochemistry, respectively.…”
Section: Methodsmentioning
confidence: 99%